An analysis of wildfire risk and historical occurrence for a mediterranean biosphere reserve, Central Chile - Bańales-Seguel, Camila; De La Barrera, Francisco; Salazar, Alejandro (Journal of Environmental Engineering and Landscape Management, 2018)
Wildfires are one of the main processes that currently shape Mediterranean ecosystems. The analysis of wildfire risk combined with historical records allows for a greater understanding of trends and their relation to territorial variables that are favourable to future events. Using GIS analysis, we assess wildfire risk in La Campana – Peñuelas Biosphere Reserve, in Central Chile. Additionally, with official historical records and LANDSAT satellite images from 1985–2015 and GIS we determine historical occurrence in the Reserve. We found that the areas with very high risk of wildfire occurrence have a strong combination of ignition factors such as presence of human settlements and road connectivity, and variables that would be negatively impacted by the occurrence of wildfires, such as degraded soils and vulnerable vegetation. These findings highlight the need to destine resources to fire prevention in these areas and develop adaptation strategies for risk management at different scales.